Allele Diversity of Diiti Cattle Using Microsatellite Loci - Dako, Safriyanto; Nibras Karnain Laya; Syahruddin Syahruddin; Ari Ardiantoro; Desinta Wulandari; Suyadi suyadi (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
Diiti cattle or Gorontalo local cattle were cattle that have the same exterior characteristics like Bali and PO cattle. To provide information regarding the unknown state of Diiti cattle, allele diversity was evaluated using ILSTS017, HEL13 and BM1818 microsatellite loci. A total of 117 Diti cattle from Gorontalo, Bonebolango and North Gorontalo were used in this study. Allele diversity analysis was generated using Cervus 3.0.7 version. All microsatellite loci were found to be highly polymorphic in the population. A total of 26 alleles were observed, which ranged from 6 in HEL13 and to 11 in ILSTS017. The mean of total alleles was found 6.667. The expected heterozygosity and observed heterozygosity values were 0.686, 0.610, 0.818 and 0.512, 0.351, 0.721 in ILSTS017, HEL13 and BM1818, respectively. Polymorphism Information Content (PIC) values were 0.540 for HEL13, 0.645 for ILSTS017 and 0.791 for BM1818. The result of this study would be used as basic information for development of unknown state of Diiti cattle as Gorontalo valuable genetic resources.